Neoliberalismo e educação: a precarização do trabalho docente e da educação pública no estado de São Paulo - Simardi Neto, Moacir (2019)
This paper aims to analyze the developments of neoliberalism in its political-educational, pedagogical and legal aspects in the state of São Paulo during the administration of the Brazilian Social Democracy Party (PSDB), which has ruled the state for twenty-four years and, in the last elections, got another mandate. It is noteworthy that, alongside the implementation of such policies, social struggles and resistances in the field of education were found in antithesis to the implantation of the neoliberal project for the education of São Paulo and will be verified by means of interviews with professors who occupy positions towards the Union of Teachers of the Official Teaching of the State of São Paulo (APEOESP). The analysis of the relationship between neoliberalism and education in the state of São Paulo and the social struggles in this field points to the possibilities of an emancipatory project that is opposed to the precariousness of teaching work and public education.